Dynamic changes in cardiac morphology, function, and diffuse myocardial fibrosis duration of diabetes in type 1 and type 2 diabetic mice models using 7.0 T CMR and echocardiography - Zhang, Hong-Kai; Shi, Chun-Yan; Liu, Dong-Ting; Gao, Hui-Qiang; Zhao, Qian-Qian; Zhang, Nan; Yang, Lin; Li, Guo-Qi; Wang, Yue-Li; Du, Yu; Li, Qing; Bo, Kai-Rui; et al. (Frontiers in Endocrinology, 2023)
Background Diabetes mellitus (DM) is associated with an increased risk of cardiovascular disease (CVD). Hence, early detection of cardiac changes by imaging is crucial to reducing cardiovascular complications. Purpose Early detection of cardiac changes is crucial to reducing cardiovascular complications. The study aimed to detect the dynamic change in cardiac morphology, function, and diffuse myocardial fibrosis(DMF) associated with T1DM and T2DM mice models. Materials and methods 4-week-old C57Bl/6J male mice were randomly divided into control (n=30), T1DM (n=30), and T2DM (n=30) groups. A longitudinal study was conducted every 4 weeks using serial 7.0T CMR and echocardiography imaging. Left ventricular ejection fraction (LV EF), tissue tracking parameters, and DMF were measured by cine CMR and extracellular volume fraction (ECV). Global peak circumferential strain (GCPS), peak systolic strain rate (GCPSSR) values were acquired by CMR feature tracking. LV diastolic function parameter (E/E’) was acquired by echocardiography. The correlations between the ECV and cardiac function parameters were assessed by Pearson’s test. Results A total of 6 mice were included every 4 weeks in control, T1DM, and T2DM groups for analysis. Compared to control group, an increase was detected in the LV mass and E/E’ ratio, while the values of GCPS, GCPSSR decreased mildly in DM. Compared to T2DM group, GCPS and GCPSSR decreased earlier in T1DM(GCPS 12W,P=0.004; GCPSSR 12W,P=0.04). ECV values showed a significant correlation with GCPS and GCPSSR in DM groups. Moreover, ECV values showed a strong positive correlation with E/E’(T1DM,r=0.757,P<0.001;T2DM, r=0.811,P<0.001). Conclusion The combination of ECV and cardiac mechanical parameters provide imaging biomakers for pathophysiology, early diagnosis of cardiac morphology, function and early intervention in diabetic cardiomyopathy in the future.